Extant coccolithophores around Azores Archipelago during Meteor cruise M150 - Aurea Narciso; Manfred Kaufmann; Barbara Springer; Teresa Lopes Silva; Kai Horst George (PANGAEA, 2023)
A systematic investigation of the extant coccolithophore community around Azores Archipelago was performed during the cruise M150 of FS Meteor between August, 27, and October, 2, 2018, in the scope of the project BIODIAZ - Controls in benthic and pelagic BIODIversity of the AZores. For the description of the spacial and vertical distribution of the extant coccolithophore community sampling was done at 50 stations along 9 transects including 3 islands, a seamount and islets from 5 to 8 water depths between surface and 150 m. A total of 306 samples were obtained, filtered onboard onto polycarbonate membranes and sections of these filters mounted in the laboratory on microscope slides for analysis by cross-polarized light microscopy. At least 400 coccospheres were counted through a randomly selected sequence of fields of view and the absolute abundances (Coccospheres/L) were estimated.